Nurses defending the autonomy of the elderly at the end of life - Rafael Barroso Gaspar; Marcelle Miranda da Silva; Karen Gisela Moraes Zepeda; Ítalo Rodolfo Silva (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to understand how nurses deal with the elderly's autonomy at the end of life. Method: qualitative, exploratory study, guided by the Grounded Theory. Ten nurses, eight doctors and 15 nursing technicians were interviewed between November 2016 and May 2017 at a university hospital in Rio de Janeiro/Brazil. Results: nurses deal with the elderly's autonomy in compliance with the code of ethics and exercise leadership in actions and interactions to defend this right, evaluating, guiding and listening to the preferences of the elderly; interacting with the family; and sharing information with the health team. Final considerations: the elderly's autonomy must be ensured in care planning, based on patient-centered communication and developed in the interaction among agents involved in care. The discussion on "Living Wills" Health Care Directives and principles of palliative care must be encouraged.